Advancement of Megadunes and its Implications in the Badain Jaran Sand Sea - Dong, Peng; Liang, Aimin; Zhou, Yali (Frontiers in Earth Science, 2022)
The tallest megadunes on the Earth are developed in China’s Badain Jaran Sand Sea, and curiosity arises whether such large dunes migrate. Hower, our present understanding of movement of aeolian bedforms is largely limited to dunes with height ranging from several to several tens of meters. Difficulties in understanding megadune movement largely lie in monitoring methods. This paper presents the evidence of the megadune advance and its rate in the Badain Jaran Sand Sea, estimated by OSL dating of sediments on slipfaces of several megadunes. It is suggested that megadunes experience similar advance to sand dunes commonly observed; the advance rate of megadunes fits the rate-height relationship that advance rate changes linearly with the reciprocal of megadune height, which has been confirmed for dunes, extending the advance rate-height relationship to a previously blind range of dune size. The advance rate of megadunes also has far-reaching implications for megadune formation. In combination with other morphometric evidences, it enhances the belief that the development of megadunes is predominantly controlled by wind rather than other factors such as the underlying relief and ground water held by most researchers.